Perceptions of patients in the waiting line for bariatric surgery: contributions from the experience of an educational process - Evangelista, Mayara Martins; Dos Santos, Loiane Letícia; Barradas, Nayara Cabral; Buzello, Ludmila Crespo; Ito, Iara Tocico; Vieira, Carla Maria [UNESP]; de Oliveira, Maria Rita Marques [UNESP] (FapUNIFESP (SciELO), 2022)
The present study is a qualitative research with the objective of analyzing the perceptions of patients in the face of the challenges in the bariatric surgery line through focal groups. All patients were treated with an outpatient protocol, however, they were divided into two groups, one participated in the educational process and the other did not. Four categories of analysis were drawn up and discussed in the light of the current literature. Patients from the educational process were able to express themselves with greater positivity in view of the challenges and they showed better resources for going through the emotional suffering, the worsening of comorbidities and the risk of death. The results show the potential of education in health and of group work in the promotion of self-care and well-being.
Percepciones de pacientes en la fila de espera para cirugía bariátrica: contribuciones a partir de la experiencia de un proceso educativo
Percepções de pacientes na fila de espera para cirurgia bariátrica: contribuições a partir da experiência de um processo educativo
Keywords: Bariatric surgery; Focus group; Health education; Obesity; Qualitative research